Teachers’ Perceptions of The Independent Learning Policy at SMP Negeri 4 Lembang Jaya, Solok Regency - Nursaid; Ningsih, Ayu Gustia; Rahman, Aida Fitri (Graduate Program Magister Manajemen Pendidikan, 2023)
This study examines Teacher Perceptions of the Freedom to Learn Policy, especially regarding the Simplification of Learning Implementation Plans (RPP) at SMP Negeri 4 Lembang Jaya, Solok Regency. The purpose of this study was to find out how the teacher’s perception of the Free Learning Policy regarding the Simplification of Learning Implementation Plans (RPP) at SMP Negeri 4 Lembang Jaya, Solok Regency. In this research, there are 3 formulations of the problem, namely what is the teacher’s perception of the independent learning policy regarding simplification of lesson plans in SMP Negeri 4 Lembang Jaya, Solok Regency, and what are the obstacles faced by teachers in preparing lesson plans, and what are the solutions to these problems. This type of research is descriptive qualitative research. The results showed that teachers’ perceptions of the independent learning policy regarding simplification of lesson plans, namely that the existence of this policy of simplifying lesson plans really helped teachers in terms of administration which did not take much time in preparing lesson plans. Whatever the obstacles in the preparation of lesson plans that will be simplified, namely the lack of socialization and adequate skill abilities by teachers related to writing 1 sheet lesson plans and the different formats in writing lesson plans from the previous curriculum. The solution taken by the school to overcome these obstacles is to hold socialization about writing lesson plans and holding MGMPs every week for each subject teacher.